Delta Systolic Blood Pressure (SBP) Can be a Stronger Predictor of Mortality Than Pre-Aortic Occlusion SBP in Non-Compressible Torso Hemorrhage: An Abotrauma and Aorta Analysis. (21st December 2021) - Duchesne, Juan; McGreevy, David; Nilsson, Kristofer; DuBose, Joseph; Rasmussen, Todd E.; Brenner, Megan; Jacome, Tomas; Hörer, Tal; Tatum, Danielle
ABSTRACT: Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is becoming a standardized adjunct for the management in patients with severe non-compressible torso hemorrhage (NCTH). Although guidelines have been developed to help with the best indications for REBOA utilization, no studies have addressed the significance of change in systolic blood pressure (ΔSBP) after REBOA insufflation. We hypothesized that ΔSBP would predict mortality in patients with NCTH and have utility as a surrogate marker for hemorrhage status. Study Design: This was an international, multicenter retrospective review of all patients managed with REBOA from the ABOTrauma Registry and the AORTA database. ΔSBP was defined as the difference between pre- and post-REBOA insertion SBP. Based on post-insertion SBP, patient hemorrhage status was categorized as responder or non-responder. A non-responder was defined as a hypotensive patient with systolic blood pressure < 90 mm Hg after REBOA placement with full aortic occlusion. Significance was set at P < 0.05. Results: A total of 524 patients with NCTH were included. Most (74%) were male, 77% blunt injured with a median age of 40 (27–58) years and Injury Severity Score 34 (25–45). Overall mortality was 51.0%. Twenty percent of patients were classified as non-responders. Demographic and injury descriptors did not differ between groups. Mortality was significantly higher in non-responders versus responders (64% versus 46%, respectively; P = 0.001). Non-responders had lower median pre-insertion SBP (50 mm Hg vs. 67 mm Hg; P < 0.001) and lower ΔSBP (20 mm Hg vs. 48 mm Hg; P < 0.001). Conclusion: REBOA non-responders present and remain persistently hypotensive and are more likely to die than responders, indicating a potential direct correlation between ΔSBP as a surrogate marker of hemorrhage volume status and mortality. Future prospective studies will need to further elucidate the impact of Damage Control Resuscitation efforts on ΔSBP and mortality.